2014
DOI: 10.1089/jmf.2013.0069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chios Mastic Gum on Lipid and Glucose Metabolism in Diabetic Mice

Abstract: Chios mastic gum (MG), a resin produced from Pistacia lentiscus var. Chia, is reported to possess beneficial cardiovascular and hepatoprotective properties. This study investigated the effect of crude Chios MG on metabolic parameters in diabetic mice. Streptozotocin-induced diabetic 12-week-old male C57bl/6 mice were assigned to three groups: NC (n=9) control; LdM (n=9) animals receiving low dose mastic for 8 weeks (20 mg/kg body weight [BW]); and HdM (n=9) animals receiving high dose mastic (500 mg/kg BW) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
2
13
0
8
Order By: Relevance
“…Therefore, masticadienonic and isomasticadienonic acids are suggested to act as competitive 11β-HSD1 inhibitors, like carbenoxolone. The findings of this study show that the oleoresin of P. lentiscus (mastic gum), and especially masticadienonic and isomasticadienonic acids, target 11β-HSD1, which may contribute to a lowered blood glucose and improved serum fatty acids concentrations that have been observed in earlier reports on the treatment of diabetic mice with mastic gum [9]. Moreover, moronic acid, one of the triterpenes present in mastic gum [4], has been shown to exert antihyperglycemic properties in rats and to be a weak 11β-HSD1 inhibitor in vitro (22% enzyme inhibition at the concentration of 10 µM) [36].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, masticadienonic and isomasticadienonic acids are suggested to act as competitive 11β-HSD1 inhibitors, like carbenoxolone. The findings of this study show that the oleoresin of P. lentiscus (mastic gum), and especially masticadienonic and isomasticadienonic acids, target 11β-HSD1, which may contribute to a lowered blood glucose and improved serum fatty acids concentrations that have been observed in earlier reports on the treatment of diabetic mice with mastic gum [9]. Moreover, moronic acid, one of the triterpenes present in mastic gum [4], has been shown to exert antihyperglycemic properties in rats and to be a weak 11β-HSD1 inhibitor in vitro (22% enzyme inhibition at the concentration of 10 µM) [36].…”
supporting
confidence: 70%
“…An in vivo study in rats indicated that daily consumption of mastic gum resulted in a 40% decrease of blood glucose levels in high-fat dietfed rats that also received streptozotoxin injection according to a protocol that induced diabetes II [8]. In addition, the administration of mastic gum decreased blood glucose levels and improved serum fatty acid levels in diabetic mice [9]. Nevertheless, it is likely that these effects are not only mediated through PPARγ.…”
Section: Abbreviationsmentioning
confidence: 99%
“…ethnomedicine and ethnobiology propensities were comprehensively reviewed , mainly highlighting the pharmacological significance and relevance of this species. Recently, P. lentiscus chios mastic gum could markedly improve glucose and lipid metabolism‐associated disturbances in STZ‐diabetic mice while alleviating hepatic damage . This can be linked to the pronounced antioxidative properties of P. lentiscus .…”
Section: Resultsmentioning
confidence: 99%
“…In the aforementioned study of 179 healthy Greek male subjects, Kartalis et al [19] showed that glucose levels were reduced in the group that received the relatively low daily dose of 1 g CMG. Conversely, in diabetic mice, both low and high doses of mastic powder (fed for 8 weeks) substantially reduced blood glucose levels [18].…”
Section: Resultsmentioning
confidence: 93%
“…Vallianou et al [15] reported that the administration of CMG essential oil to hyperlipidemic rats reduced TG, TC, and LDL-C concentrations by 65.4, 59.9, and 72.5%, respectively, and attributed this result to the camphene content of CMG. Georgiadis et al [18] fed diabetic mice with low or high doses of mastic powder for 8 weeks, and showed that TG was significantly reduced in both groups, and TC and LDL-C were significantly reduced in the low-dose group. In human studies, the effects of CMG on TG and other lipids are less consistent.…”
Section: Resultsmentioning
confidence: 99%